A comparative analysis of the provision of student housing safety measures. Issue 3 (22nd February 2021) - Simpeh, Fredrick; Akinlolu, Mariam
Abstract : Purpose: Security, safety, environment and health have become an integral part of facility management (FM). Therefore, FM departments within organisations are required to put measures in place to safeguard facility users. This paper thus aims to investigate and compare the safety and security measures that are provided in the student housing of two universities in South Africa. Design/methodology/approach: A mixed method approach was adopted; interview was used to collect qualitative data, whereas a questionnaire was used as an instrument to collect quantitative data. Content analysis was used to analyse the qualitative data, whereas both descriptive and inferential statistics were used to analyse the quantitative data. Findings: It became evident that university B had a better provision of safety and security measures in the student housing than university A. The study also found that both universities had some lapses in the safety and security measures provided in the student housing. Measures that were lacking in both universities were weapon detector, closed-circuit television (CCTV), water sprinkler system, burglar bars on the doors, lift for disabled students, disabled toilet facility, traffic light, tags for vehicles, first aid box, accident book and medically trained personnel. Research limitations/implications: Data were collected from only two universities, making it difficult to generalise the findings of the research. For a broader perspective, a study that expands the number of participating universities is recommended. Practical implications: The facility management and safety department in the universities can use the recommendations to improve on the safety and security measures required in the student housing. Moreover, the recommendations can contribute to the development of policy frameworks for student housing safety. Originality/value: There is a paucity of studies on student housing safety/security worldwide, and South Africa in particular. With this study, the authors contribute to the body of knowledge in this area of research.